Security for smart cities. Issue 2 (13th May 2020) - Toh, Chai K.
Abstract : Smart cities are evolving globally and many governments have invested large sums of monies to develop smart cities. This development is not a result of an overnight decision but rather, smart cities have evolved through a period of time, directly from earlier work on the digital city to ubiquitous city, green city, connected city, sustainable city, eco‐city etc. The present age sees the arrival of very high‐speed wireless 5G connectivity, fast GPU multi‐core‐based servers, big data, cloud computing, artificial intelligence, and data analytics. Many of these new technologies have supported the development and realisation of smart cities. In this study, the authors present an outline of security for smart cities and provide a deeper understanding of what we meant by securing smart cities. They discuss the applicability of existing security methods of authentication, access control, encryption, firewalls, and their appropriateness to defending a smart city. Specifically, we cover the security of data, internet, water supply, electricity supply, city brain, and other critical city services and present the possible malicious attacks on a smart city and consequences. Finally, they discuss security best practices for smart cities.